2010
DOI: 10.1620/tjem.221.29
|View full text |Cite
|
Sign up to set email alerts
|

Low Body Mass Index and Low Serum Albumin Are Predictive Factors for Short-Term Mortality in Elderly Japanese Requiring Home Care

Abstract: Japan has a rapidly growing elderly population. The proportion of citizens aged 65 years and over was 22.1% in 2008, and is projected to as high as 27% by 2015 (Health and Welfare Statistics Association 2009). In accordance, elderly individuals requiring care are also increasing. To cope with this situation, the long term care service system was implemented in Japan in 2000. Since then, the number of elderly requiring care doubled from 2.2 to 4.4 million (Health and Welfare Statistics Association 2008).One of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 22 publications
2
27
0
1
Order By: Relevance
“…Nevertheless, hypoalbuminaemia in our study was found to be associated with mortality as an independent predictor of death; each decrease in albumin by 1·0 g/l was associated with a 3 % increase in mortality (20) . Similar data have been shown in studies of patients with end-stage renal disease (21) , after hip fracture (22) or in frail elderly patients (23) . Malnutrition is commonly associated with certain diseases (24,25) , so we explored the prevalence of malnutrition estimated by SGA among the co-morbidities.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, hypoalbuminaemia in our study was found to be associated with mortality as an independent predictor of death; each decrease in albumin by 1·0 g/l was associated with a 3 % increase in mortality (20) . Similar data have been shown in studies of patients with end-stage renal disease (21) , after hip fracture (22) or in frail elderly patients (23) . Malnutrition is commonly associated with certain diseases (24,25) , so we explored the prevalence of malnutrition estimated by SGA among the co-morbidities.…”
Section: Discussionsupporting
confidence: 86%
“…In the elderly living in the community there is a clear association between albumin levels and long-term mortality (between 3 and 12 years) [13,33,[58][59][60][61]. However, in the elderly living in care homes albumin was associated to short-term mortality (1 year) but not to long-term mortality [13].…”
Section: In Community-dwelling Elderly and In Nursing-home Residentsmentioning
confidence: 99%
“…3 – 6 In Japan, several research groups have reported that low ADL levels are associated with high mortality in elderly populations. 3 , 7 – 12 However, these studies were conducted exclusively in community settings and not in institutional settings.…”
Section: Introductionmentioning
confidence: 99%